Effect of HBA1C on Cognitive Skills in Type 2 Diabetic Patients Received at Liaquat University Hospital - Almani, Suhail Ahmed; Nazia, Shafaq; Shah, Muhammad Iqbal; Abbasi, Madiha; Kumar, Santosh; Feroze, Zohaib (Journal of Liaquat University of Medical & Health Sciences, 2022)
Objective: To determine the effect of HbA1c on cognitive skills of type 2 diabetic patients received at Liaquat University Hospital, Jamshoro. Methodology: The retrospective Cohort study was conducted on 278 patients received at Liaquat University Hospital, Jamshoro from September 2019 to March 2020. Sampling technique was non probability, consecutive. The inclusion criteria were both genders age more than 18 years and diabetes mellitus type 2 while the exclusion criteria were other causes of cognitive impairment including thyroid disease, psychiatric illness, alcohol intake, smoking, dementia, delirium, dyslipidemia, ischemic heart disease, stroke, anemia, and pregnancy. A proforma was used to collect data including Hemoglobin A1c and score obtained on General Practitioner Assessment of Cognition Scale. Analysis was done using SPSS 20. This study was funded by the authors. Results: About 55.76 % participants were males. Mean [SD] age was 54.7 [5.4] years, diabetes duration was 8.7 [5.2] years. Baseline HbA1c ranged from 4.1% to 13.2%. A number of 96 patients (34.53%) were cognitively impaired as assessed by General Practitioner Assessment of Cognition Scale. Out of these, 79 patients (82.29%) had elevated HbA1c. Conclusion: Significant association was seen between elevated HbA1C andcongitive impairment in patients with type 2 diabetes mellitus received at medical wards of Liaquat University Hospital, Jamshoro. Key Words: HBA1C (Hemoglobin A1c), Type 2 Diabetes Mellitus, Cognitive Function